Joint Singing as a Means of Cultural Transmission in Estonia - Raudsepp, Inge; Sepp, Anu; Roukonen, Inkeri (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The phenomenon of joint singing, originating from the traditional old folk song and subsequent choral singing, has developed in Estonia into a significant cultural metaphor– Song Celebrations. Recent decades have brought about rapid changes in Estonian socio-cultural reality: the process of globalisation has raised the question of how to maintain national identity and cultural traditions considering these rapid processes.The aim of this article is to analyse phenomena of joint singing and Song Celebrations through historical, cultural and educational lens. The subject and corresponding literature were analysed using hermeneutic approach by M. Heidegger, W. Dilthey and H.-G. Gadamer, reflected through the focus of culture and cultural transmission by L.Rauhala, R.McShea, M.J. Taylor and C. A. Thoth.  The drifts of the content and developmental tendencies of joint singing and Song Celebrations between 1962−2011 were investigated by means of comparative analysis.The phenomenon of joint singing that has developed into the Song Celebrations tradition continues to be one the main means of cultural transmission in Estonia.